2016
DOI: 10.1002/adem.201600650
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Lead Borate Single Crystal Nanosheets for Attenuating Both Neutron and Gamma Radiations

Abstract: In this work, Pb 3 B 10 O 16 [OH] 4 single crystal nanosheets are fabricated by a solvothermal process. Its structure is determined in detail by XRD, SEM, and TEM. The nanosheets display a good ability to attenuate both neutron and gamma radiations. In particular, it provides a distinct advantage to attenuate the gamma radiation with low energy from 59 to 105 keV. Notably, the lead borate single crystals with 2D nanostructures impliy other benefits, such as mechanical enhancement and high thermal conductivity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Recently, using an organic acid as both a coordinating reagent and a soft template has been an effective way of fabricating metal oxides [21,22]. Studies have shown that boric acid is capable of coupling with the metal ions of Pb 2+ , Cd 2+ , and Fe 2+ to form nanosheet complexes [23][24][25]. Carboxylphenyl boronic acid was reported to complex with metal ions (such as Zn 2+ , Cd 2+ , Ni 2+ , abd Ln 3+ ) to form 2D coordination polymer nanosheets [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, using an organic acid as both a coordinating reagent and a soft template has been an effective way of fabricating metal oxides [21,22]. Studies have shown that boric acid is capable of coupling with the metal ions of Pb 2+ , Cd 2+ , and Fe 2+ to form nanosheet complexes [23][24][25]. Carboxylphenyl boronic acid was reported to complex with metal ions (such as Zn 2+ , Cd 2+ , Ni 2+ , abd Ln 3+ ) to form 2D coordination polymer nanosheets [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…These properties provide diverse applications in opto-electronic technologies such as laser frequency conversion [4], optical parameter oscillation [5] and signal communication [6]. Lead borates are of special interest in the search for borate materials, since these compounds have pronounced radiation shielding properties [7][8][9].…”
Section: Introductionmentioning
confidence: 99%